Removal of Cr(VI) and As(V) from aqueous solutions by HDTMA-modified zeolite Y - Mohd. Yusof, Alias (Elsevier BV, 2008)
The synthesized zeolite NaY from rice husk ash (RHA) and the commercial zeolite NaY both modified with surfactants in amounts equal to 50%, 100% and 200% of their external cation exchange capacity (ECEC) were used to remove chromate and arsenate anions from aqueous solutions. While the unmodified zeolite Y had little or no affinity for the Cr(VI) and As(V) anionic species, the surfactant-modi fled zeolite Y (SMZY) showed significant ability to remove of these anions from the aqueous solutions. The highest chromates and arsenates adsorption efficiency was observed from solutions of pH values 3 and 8, respectively because of the dominance of the univalent species of both anions. The adsorption equilibrium data were best fitted with the Langmuir isotherm model with the highest removal capacities observed for the SMZY initially prepared considering the hexadecyltrimethyl ammonium (HDTMA) amount equal to the 100% of the ECEC of zeolite Y. Synthesized SMZY remove Cr(VI) and As(V) more than the corresponding commercial one due to its lower silica to alumina ratio. Thus, the HDTMA-covered modified zeolite Y synthesized using RHA can be used to remove Cr(VI) and As(V) from water.